Metode Muhammad Al-Ghazali dalam Menggali Maqasid Al-Qur'an - Abdul Mufid (El-Afkar: Jurnal Pemikiran Keislaman dan Tafsir Hadis, 2020)
This study aims to explore the main milestones of the method used by Muhammad al-Ghazali to reveal the Qur'anic maqasid by answering a number of questions as follows: Does al-Ghazali have a special method in approaching the Qur'anic maqasid? If it turns out there really is a special method, what are the advantages and characteristics of the method? What are the main features? How far the method was successfully applied in several studies and studies of the Koran. This research aims to explore the main milestones of the method used by Muhammad al-Ghazali to reveal the Qur'anic maqasid by answering a number of questions as follows: Does al-Ghazali have a special method in approaching the Qur'anic maqasid? If it turns out there really is a special method, what are the advantages and characteristics of the method? What are the main features? How far the method has been successfully applied in several studies and studies of the Koran. The result s showed that al-Ghazali offered five methods to be able to reveal the qur’anic maqasid. First, deep reflection on the qur’anic texts and optimizing reason. Second, the use of two mechanisms at the same time, namely inductive thinking and analysis, and tracking various texts and signs that indicate the existence of maqasid. Third, a thorough reading of the revelation texts so that they are holostic, not literal and sectarian. Fourth, always mingle with the Koran while interrogating the verses to explore the depth of their meaning. Fifth, devoting the ability to produce fiqh of reality